Salience and taxation theory and evidence - Chetty, Raj 1979-; Looney, Adam; Kroft, Kory (National Bureau of Economic Research, 2007)
A central assumption in public finance is that individuals optimize fully with respect to the incentives created by tax policies. In this paper, we test this assumption using two empirical strategies. First, we conducted an experiment at a grocery store where we posted tax-inclusive prices for 750 products subject to sales tax for a three week period. Using scanner data, we find that posting tax-inclusive prices reduced demand by roughly 8 percent among the treated products relative to control products and nearby control stores. Second, we find that state-level increases in excise taxes (which are included in posted prices) reduce aggregate alcohol consumption significantly more than increases in sales taxes (which are added at the register and hence less salient). Both sets of results indicate that tax salience affects behavioral responses. We propose a bounded rationality model to explain why salience matters, and show that it matches our evidence as well as several additional stylized facts. In the model, agents incur second-order (small) utility losses from ignoring some taxes, even though these taxes have first-order (large) effects on social welfare and government revenue. Using this theoretical framework, we develop elasticity-based formulas for the efficiency cost and incidence of commodity taxes when agents do not optimize fully.